Haloacetic acids and other disinfection by-products in UK treated waters : occurence, formation and precursor investigation - Bougeard, Cynthia (Cranfield University, 2009)
Disinfection by-products (DBPs) in drinking water are formed when natural organic matter (NOM) that remains after initial treatment reacts with disinfectants, such as chlorine or chloramines. DBPs, which are of health concern, can take the form of trihalomethanes (THMs), haloacetic acids (HAAs), haloacetonitriles (HANs), haloketones (HKs), haloacetaldehydes (HAs), halonitromethanes (HNMs) and a host of other halogenated DBPs. So far, regulations in the United Kingdom (UK) only encompass the group of THMs allowing a maximum level of 100 µg/L. HAAs, the second most prevalent class of DBPs, are currently under consideration by the European Union to be regulated at 80 µg/L. Reliable and reproducible quantification methods are required for DBP detection. To address this need, the presented work includes a comparative study between analytical devices, which concludes that GC/ECD is the only approach with suitable detection limits. This work reports an investigation of the DBP formation potential (FP) of waters from 11 water treatment works (WTWs) at different locations in the UK. Several of these waters have shown to form significant levels of HAAs and THMs. Furthermore, other DBPs, such as iodo-THMs (i-THMs), HANs, HKs, HAs and HNMs were detected. It has also been confirmed that improving the control of these DBPs can be achieved by using monochloramine instead of free chlorine. A statistical analysis revealed that THMs correlated well with the HAAs, and as a result the regulatory limit of 100 µg/L for the THM4 would fail a regulation of 80 µg/L for the nine HAAs. A number of parameters have been identified, which have particular relevance when considering the formation of HAAs and THMs in treated waters. Threshold bromide level was determined beyond which speciation of DBPs shift toward brominated species. The pH, which significantly affected THMs, was less strongly linked to the HAAs. The temperature had a consistent impact with a decreasing DBP formation at lower temperatures. Increasing the contact time with the disinfectant resulted in parallel first order reaction kinetics of the HAAs and THMs. Finally, the precursors involved in the formation of DBPs were found to be specific to water sources.